Narrativa transmedia: noamor casos de femicidio en la provincia de El Oro - Ramón Romero, Jenniffer Mishel (Machala, 2020)
This paper deals with a problem that has occurred throughout the world such as femicide; however, we bring something different, that is, a communicational proposal scheme based on transmedia narrative about femicide; focused on the development of content especially for the male audience of the province of El Oro. The creation of communication products, to reach our audience, the different and special thing is that its diffusion will be through an interface, and a narrative. In many parts of the world there are different campaigns, organizations that defend women and therefore are against femicide, and their primary audience is women, victims, and campaigns for men and family are not developed. This work is directed towards the development of the transmedia narrative, with men as a priority, since after an investigation carried out where the cases of femicide, causes, consequences, and studying male patterns have been identified, it was possible to characterize which platforms, the means correct and adequate so that communicational products can raise awareness about femicide, when they arrive in the planned way. For the execution of this project, a media coverage of the different cases of femicide which occurred in Machala was carried out. A debate was also held among teachers of the Social Communication career at the Technical University of Machala. Interviews with professionals in the area such as Social Communicators, Producers, Journalists, served to create the transmedia narrative. On the other hand, the focus groups allowed to identify the interfaces to be used in the dissemination of the products. We apply a methodology with a mixed, qualitative approach since the research consists in reconstructing the reality of femicide cases through a transmedia narrative to reach our primary audience, the male audience of the province of El Oro. Quantitative is to measure the results of the proposal at the time of applying it, through metrics. The scope of the research is descriptive since it consists in describing the different cases of femicide in the Province of El Oro. The research design is non-experimental, because there is no non-manipulation of the variable, but we observe the phenomenon as and as they occur in context And it has a non-probabilistic sampling, since there is no complete list of the audience, but men who are in a relationship or married, from the age of 25 to 55 years. Through the transmedia narrative, the aim is to sensitize the audience, in addition to becoming prosumers of content that helps the assimilation and awareness of femicide.
El presente trabajo trata una problemática que se ha dado en todo el mundo como es el femicidio; sin embargo, traemos algo diferente, es decir una propuesta comunicacional basada en narrativa transmedia sobre el femicidio enfocado en el desarrollo de contenidos en especial en la audiencia masculina de la provincia de El Oro. La creación de productos comunicacionales, para llegar a nuestra audiencia, lo diferente y especial, es que su difusión será por medio de una interfaz, y una narrativa. En muchas partes del mundo existen diferentes campañas, organizaciones que defienden a la mujer y por ende están en contra del femicidio, y su audiencia primaria son las mujeres, las víctimas, y no se desarrolla campañas para los hombres y familiares. Este trabajo está dirigido hacia el desarrollo de la narrativa transmedia teniendo como prioridad a los hombres, ya que tras una investigación realizada donde se ha identificado los casos de femicidio, causas, consecuencias, y estudiar los patrones masculino, permitió caracterizar cuáles plataformas, los medios correctos y adecuados para que los productos comunicacionales puedan sensibilizar sobre el femicidio, cuando lleguen a la forma planificada. Para la ejecución de este proyecto, se realizó una cobertura mediática de los diferentes casos de femicidio ocurridos en Machala, también se desarrolló un debate entre docentes de la carrera de Comunicación Social de la Universidad Técnica de Machala. Las entrevistas a profesionales en el área como Comunicadores Sociales, Productores, Periodistas, sirvió para crear la narrativa transmedia. Por otro lado, los grupos focales permitió identificar las interfaces para utilizar en la difusión de los productos. Aplicamos una metodología con un enfoque mixto, cualitativo ya que la investigación consiste en reconstruir la realidad de los casos de femicidio por medio de una narrativa transmedia para llegar a nuestra audiencia primaria, la masculina de la provincia de El Oro. Cuantitativo es para medir los resultados de la propuesta al momento de aplicarla, por medio de las métricas. El alcance de la investigación es descriptivo ya que consta en describir los diferentes casos de femicidio en la Provincia de El Oro. El diseño de investigación es el no experimental, porque no existe la no manipulación a la variable, sino que observamos el fenómeno tal y como se dan en su contexto. Y posee un muestreo no probabilístico, ya que no se cuenta con un listado completo de la audiencia, sino hombres que estén en una relación o casados, de la edad de 25 hasta los 55 años. Por medio de la narrativa transmedia se pretende llegar sensibilizar a la audiencia, además de convertirse en prosumidores de contenidos que ayuden a la asimilación y conciencia de del femicidio. Por medio de la narrativa transmedia se pretende llegar sensibilizar a la audiencia, además de convertirse en prosumidores de contenidos que ayuden a la asimilación y conciencia de del femicidio. Por medio de la narrativa transmedia se pretende llegar sensibilizar a la audiencia, además de convertirse en prosumidores y evangelizadores de contenidos que ayuden a la asimilación y sensibilización de del femicidio.
Keywords: FEMICIDIO; NARRATIVA TRANSMEDIA